Effect of low-fluoride dentifrices supplemented with calcium glycerophosphate on enamel demineralization in situ - Amaral, Jackeline Gallo D.O.; Sassaki, Kikue Takebayashi; Martinhon, Dbstphu Cleide Cristina Rodrigues; Delbem, Alberto Carlos Botazzo [UNESP] (My University, 2013)
Purpose: To evaluate whether a low-fluoride dentifrice with calcium glycerophosphate (CaGP) reduced the demineralization process in situ. Methods: A cross-over design with four treatment phases of 7 days each was used. Ten volunteers wore palatal devices containing four blocks of bovine dental enamel. The enamel was treated (ex-vivo) with a placebo, 500 μg-F/g (500), 500 μg-F/g with 0.25%CaGP (500 CaGP), and 1,100 μg-F/g (1,100) dentifrices (twice a day/1 minute) under cariogenic challenge from sucrose solution. To evaluate mineral loss, surface and crosssectional hardness were performed. The fluoride, calcium, and phosphorus ion concentrations from enamel and dental plaque were determined. The insoluble extracellular polysaccharide (EPS) concentrations were also analyzed. The data were submitted to ANOVA (1-way) followed by the Student-Newman-Keuls test (P< 0.05). Results: The mineral loss and EPS concentration were lowest in the 500 CaGP and 1,100 dentifrice groups. The use of the 500 CaGP and 1,100 dentifrices resulted in similar fluoride, calcium, and phosphorus concentrations in the enamel and in dental plaque (P< 0.05). The ionic activities of calcium phosphate phases for the 500 CaGP and 1,100 dentifrices were similar (P< 0.492). The low-fluoride dentifrice with 0.25%CaGP demonstrated efficacy similar to that of the positive control (1,100 dentifrice) with respect to in situ demineralization.